The effectiveness of Japan's negative interest rate policy - Naoyuki Yoshino; Farhad Taghizadeh-Hesary; Hiroaki Miyamoto (Asian Development Bank Institute (ADBI), 2017)
In April 2013, the Bank of Japan (BOJ) introduced an inflation target of 2% with the aim of overcoming deflation and achieving sustainable economic growth. But due to lower international oil prices, it was unable to achieve this target and was forced to take further measures. Hence, in February 2016, the BOJ adopted a negative interest rate policy by massively increasing the money supply through purchasing long-term Japanese government bonds (JGB). The BOJ had previously purchased short-term government bonds mainly, a policy that flattened the yield curve of JGBs. On the one hand, banks reduced the numbers of government bonds because short-term bond yields had become negative, and even the interest rates of long-term government bonds up to 15 years became negative. On the other hand, bank loans to the corporate sector did not increase due to the Japanese economy's vertical investment-saving (IS) curve. This paper firstly explains why, in the view of the authors, the BOJ has to reduce its 2% inflation target in the present low oil price era. Secondly, it argues that Japan cannot make a sustainable recovery from its long-lasting recession and tackle its long-standing deflation problem by means of its current monetary policy and its negative interest rate policy in particular. It is of key importance to make the IS curve downward sloping rather than vertical. That means the rate of return on investment must be positive and companies must be willing to invest if interest rates are set too low. Japan's long-term recession is due to structural problems that cannot be solved by its current monetary policy. The last section reports our simulation results of tackling Japan's aging population by introducing a productivity-based wage rate and postponement of the retirement age, which will help the recovery of the Japanese economy.
Keywords: E43; E52; E12; 330; Economics; Finance sector development; Japan